S135 Does Cd248 Have A Role In Ipf?. (10th November 2014) - Crowley, LE; Bartis, D; Borthwick, L; Fisher, A; Thickett, DR
Abstract : Idiopathic pulmonary fibrosis (IPF) has a complex pathophysiology withepithelial-mesenchymal transition (EMT) thought to be important to the pathogenesis of fibrotic lesions. CD248 is a membrane bound receptor that has collagen and lectins as ligands and is a stromal cell marker, whose expression is up-regulated post-natally during tissue inflammation andre-modelling. A role of CD248 is emerging in kidney fibrosis, but its function in the lung is unknown. We hypothesised that CD248 is a mesenchymal marker of IPF severity and that CD248 contributes to IPF pathogenesis. Methods: CD248 expression was investigated in 23 IPF patient lung samples using immunohistochemistry (IHC) and qualitatively scored. Expression was assessed in cultured normal human lung fibroblasts (NHLFs), A549 cells, IPF derived fibroblasts and normal human primary ATIIs, treated with or without TGF-β1 and PDGF-BB, using flow cytometry and qRT-PCR. siRNA CD248 knock down (KD) on NHLF mesenchymal marker expression and proliferation was evaluated using qRT-PCR and BrdU assays. Results: IHC revealed strong CD248 expression by fibroblasts in both fibrotic areas and physiological structures of IPF lung tissue (pericytes and pleural tissue). Expression was greatest in samples from lung transplant explants. In vitro, CD248 protein levels were significantly greater in IPF derived lung fibroblasts vs NHLFs (p < 0.01). CD248 KD significantly reduced proliferation of control, PDGF-BB and/or TGF-β1 treated NHLFs (p < 0.001), but collagen and αSMA mRNA levels were unaffected (p > 0.05). The alveolar epithelium did not express CD248 on the protein level and minimal CD248 mRNA levels were detected in cultured A549 cells and ATIIs, which remained unchanged during TGF-β1 induced EMT. Summary: CD248 expression is elevated in the lungs of IPF patients especially in severe disease. CD248 expression appears specific for fibroblasts compared to epithelial cells and does not change during EMT. CD248 KD reduced fibroblast proliferation, but not myofibroblast differentiation. We conclude that CD248 over-expression is involved in the pathogenesis of IPF – and that it has potential as a marker of mesenchymal/fibroblast lineage. Given that CD248 ligands are collagen type I, IV and fibronectin, we hypothesise that CD248 signalling represents a novel matrix-fibroblast interaction that may be a potential therapeutic target in IPF.